Pengaruh Discharge Planning Terhadap Kesiapan Pasien Stroke Menghadapi Pemulangan di Ruangan Rawat Inap Neurologi - Sari, Yuli Permata (REAL in Nursing Journal, 2022)
Background: Post-stroke patients had some problems after the patient was in the middle of the family, some of the issues that will be faced by post-stroke patients at home is paralysis on one side, impaired mental status, emotional problems and communication problems, and therefore required a plan before the patient is discharged. Discharge Planning Success ensure patients are able to do follow-up care measures are safe and realistic after leaving the hospital. This study aimed to identify the influence of Discharge Planning for readiness to face the return stroke patients in the hospital room Neuro National Stroke Bukittinggi.Methods: This study used the Quasi-experimental design, with the approach of one group pre- and post-test, the samples were taken using quota sampling technique of 20 people, wearing non-parametric analysis of T-dependent.Results: The results showed that the average prior to the Discharge Planning the readiness of respondents was 24.60 with a standard deviation of 3.299. While the average after Discharge Planning the readiness of respondents was 31.50 with a standard deviation of 0.889. Visible differences between the mean readiness to face the return stroke patients before and after Discharge Planning is 6.90 with a p value of 0.000.Conclusion: Based on the conclusions of this study, should be to prepare for stroke patients in the face repatriation done that more comprehensive discharge planning.